145 Characterisation of fractionated atrial electrograms critical for maintenance of AF: a randomised controlled trial of ablation strategies (the CFAE af trial). (9th June 2011) - Hunter, R J; Diab, I; Tayebjee, M; Richmond, L; Sporton, S; Earley, M J; Schilling, R J
Abstract : Introduction: Targeting complex fractionated atrial electrograms (CFAE) in the ablation of atrial fibrillation (AF) may improve outcomes, although whether this is by eliminating focal drivers or simply de-bulking atrial tissue is unclear. It is also uncertain what electrogram morphology should be ablated. This randomised study aimed to determine the impact of ablating different CFAE morphologies compared to normal electrograms (ie, de-bulking normal tissue) on the cycle length of persistent AF (AFCL). Methods: After pulmonary vein isolation CFAE were targeted systematically throughout the left then right atrium, until termination of AF or abolition of CFAE prior to DC cardioversion. 10 s electrograms were classified by visual inspection according to a validated scale, with Grade 1 being most fractionated and grade 5 normal. Patients were randomised to have CFAE grades eliminated sequentially, from grade 1 to 5 (group 1) or grade 5 to 1 (group 2). Because grade 5 electrograms were considered normal, only 5 were ablated. Mean AFCL was determined manually over 30 cycles from bipolar electrograms recorded at the left and right atrial appendages before and after each CFAE was targeted. Lesions were regarded as individual observations, and a resultant increase in mean AFCL ≥5 ms was regarded as significant. The randomised strategy first controlled for any cumulative effect of ablation on AFCL, and second allowed assessment of the order of ablation on the number of CFAE lesions required. Results: 20 patients were randomised. The CFAE grade determined by rapid visual inspection for the 968 electrograms targeted agreed with that at off-line manual measurement in 92.7% (к=0.91). AFCL increased after targeting 49.5% of grade 1 CFAE, 33.6% of grade 2, 12.8% of grade 3, 33.0% of grade 4, and 8.2% of grade 5 CFAE (p<0.0001 for grades 1, 2, and 4 vs 5, 3 vs 5 not significant). Binary logistic regression confirmed the effect of CFAE grade, but showed no effect of electrogram amplitude, location in the left or right atrium, or the order in which CFAE were targeted. There was no difference between groups in the number of grade 1 or 2 CFAE encountered, but there were fewer grade 3 and 4 CFAE in group 2 than group 1 (both p<0.01), translating to fewer CFAE targeted per patient in group 1 compared to group 2 (37±14 and 58±18 respectively; p=0.015). Conclusion: Targeting CFAE is not simply atrial de-bulking. Ablating certain grades of CFAE caused AFCL prolongation, suggesting they are more important in maintaining AF. Targeting these CFAE may reduce unnecessary left atrial destruction. (ClinicalTrials.gov number, NCT00894400 ).